2018
DOI: 10.1371/journal.pone.0193678
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of 21 dual antimicrobial combinations comprising novel and currently recommended combinations for treatment of drug resistant gonorrhoea in future era

Abstract: BackgroundRecent WHO guidelines recommend dual therapy with ceftriaxone or cefixime plus azithromycin for gonorrhea. Azithromycin in combination with gentamicin or spectinomycin has been recommended in treatment failure cases. Due to emergence of multi-drug resistant (MDR) and extensively-drug resistant (XDR) Neisseria gonorrhoeae strains, it is important to look for efficacy of these combinations and also of others that might be used in future. Therefore, we aimed to evaluate in vitro synergy of 21 dual combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…Minimum FICI values can be found in Table S3 in the supplemental material. Our cutoff values were designed as follows: an FICI value of <0.8 represents synergy, FICI values between 0.8 and 2 represent additive interactions, FICI values between 1 and 2 represent independent interactions, and an FICI value of ≥2 represents antagonism ( 63 66 ). Isobolograms were generated by plotting the FIC A and FIC B values as x , y coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…Minimum FICI values can be found in Table S3 in the supplemental material. Our cutoff values were designed as follows: an FICI value of <0.8 represents synergy, FICI values between 0.8 and 2 represent additive interactions, FICI values between 1 and 2 represent independent interactions, and an FICI value of ≥2 represents antagonism ( 63 66 ). Isobolograms were generated by plotting the FIC A and FIC B values as x , y coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…25 Within the microbiology laboratory, studies have also examined the synergistic effect of various multi-drug combinations; for example, one such study recently evaluated 21 antimicrobial combinations and suggested five potential new dual candidate combinations, containing either gentamicin or ertapenem, for treatment of MDR and XDR N. gonorrhoeae infections. 26 Attention has once again focussed on ciprofloxacin as a potential agent for the treatment of gonorrhoea in settings where the prevalence of fluoroquinolone resistance is lower than 50%. Ciprofloxacin has the advantage that it can be prescribed as a single-dose oral regimen and it is highly efficacious in treating fluoroquinolone-susceptible gonococci in the oropharynx.…”
Section: Current Treatment Options For Gonorrhoeamentioning
confidence: 99%
“…On a similar note, Singh et al assayed the potent utility of in vitro interactions of 21 dual therapy combinations against 95 N. gonorrhoeae strains [ 23 ]. Of these 21 combinations, five were novel introductions that are not included in any existing guidelines: gentamicin + ertapenem, moxifloxacin + ertapenem, spectinomycin + ertapenem, azithromycin + moxifloxacin, and cefixime + gentamicin.…”
Section: Future Perspectivesmentioning
confidence: 99%